Education and development of rehabilitation therapy in China under the background of aging - Sun, Shuyue; Lin, Xingru; Ouyang, Xiaoyao; Cai, Weiqin; Gao, Qianqian; Guo, Peiwu; Li, Zongrun; Ji, Lihong; Dong, Zhiwei; Jing, Qi; Zhang, Jianhua (Frontiers in Public Health, 2022)
As a large country with a population of more than 1.4 billion and accounting for nearly one-third of the world, China faces multiple challenges such as a relatively high degree of population aging and rapid growth, a high incidence of chronic diseases, and an increase in the number of disabled people and postoperative rehabilitation, and the demand for rehabilitation treatment is relatively large. China has also done a lot of work in this regard in recent years and achieved good results. Starting from the perspective of China's rehabilitation treatment education system, this study studies the current development status of rehabilitation treatment education in China by combing the development status of Chinese mainland rehabilitation treatment related majors at the four educational levels of full-time (post) -undergraduate-master's degree-ph.D., and summarizes the rehabilitation treatment education model with Chinese characteristics that is suitable for the development of rehabilitation treatment in China in comparison with international rehabilitation education. On the one hand, based on the international rehabilitation-related classification concepts and method guidance, it promotes the goal and system setting of rehabilitation therapy education and training in China to continuously meet the current health needs of the population; On the other hand, the basic theories and methods of traditional Chinese medicine with Chinese characteristics will be integrated into the cultivation of disciplines related to rehabilitation and treatment. At the same time, we will accelerate the promotion of rehabilitation education by national policies, further optimize the existing rehabilitation disciplines and curriculum settings according to the requirements of relevant international education majors and curriculum settings, and enhance the international recognition of Rehabilitation Therapy education training and personnel qualifications in China. This study provides a good reference for health policy makers, leaders and scholars to formulate a more realistic rehabilitation education program in China, and even to formulate an internationally recognized rehabilitation education program.